Epidemiological profile of anti-rabies post-exposure care from wild animals’ aggressions in Pernambuco, Brazil (Research, Society and Development, 2022)
Rabies is endemic in the state of Pernambuco with the last case of the disease recorded in 2017, in the city of Recife. Since knowledge regarding the current epidemiological situation contributes to the establishment of control strategies over the disease in the state, the main objective of this study was to describe and evaluate the profile of notified human anti-rabies care, from wild animals aggressions, registered in the Notifiable Diseases Information System (SINAN) from 2011 to 2017. During the evaluation, 6,363 human anti-rabies consultations were observed, and it was possible to analyze the variables collected during the service and relate them to the Technical Norms of Human Rabies Prophylaxis from the Ministry of Health. The results revealed that adult males compose the profile most attacked with bite-like exposures and with single predominant lesions. Concerning the aggressor animal there was an increase in the incidence of aggressions from Chiropterans. It is concluded that the health actions evaluated in this work need to improve control strategies over the wild rabies cycle, with attention to bats, relevant animals in the epidemiological chain of transmission of primary and secondary forms, and improve actions in the population health education.